A Review on the Therapeutic Role of TKIs in Case of CML in Combination With Epigenetic Drugs - Amir, Mohd; Javed, Saleem (Frontiers in Genetics, 2021)
Chronic myeloid leukemia is a malignancy of bone marrow that affects white blood cells. There is strong evidence that disease progression, treatment responses, and overall clinical outcomes of CML patients are influenced by the accumulation of other genetic and epigenetic abnormalities, rather than only the BCR/ABL1 oncoprotein. Both genetic and epigenetic factors influence the efficacy of CML treatment strategies. Targeted medicines known as tyrosine-kinase inhibitors have dramatically improved long-term survival rates in CML patients during the previous two decades. When compared to earlier chemotherapy treatments, these drugs have revolutionized CML treatment and allowed most people to live longer lives. Although epigenetic inhibitors' activity is disrupted in many cancers, including CML, but when combined with TKI, they may offer potential therapeutic strategies for the treatment of CML cells. The epigenetics of tyrosine kinase inhibitors and resistance to them is being studied, with a particular focus on imatinib, which is used to treat CML. In addition, the use of epigenetic drugs in conjunction with TKIs has been discussed. Resistance to TKIs is still a problem in curing the disease, necessitating the development of new therapies. This study focused on epigenetic pathways involved in CML pathogenesis and tumor cell resistance to TKIs, both of which contribute to leukemic clone breakout and proliferation.